Daratumumab plus pomalidomide and dexamethasone versus pomalidomide and dexamethasone alone in previously treated multiple myeloma (APOLLO): an open-label, randomised, phase 3 trial. Issue 6 (June 2021) - Dimopoulos, Meletios A; Terpos, Evangelos; Boccadoro, Mario; Delimpasi, Sosana; Beksac, Meral; Katodritou, Eirini; Moreau, Philippe; Baldini, Luca; Symeonidis, Argiris; Bila, Jelena; Oriol, Albert; Mateos, Maria-Victoria; et al.
Summary: Background: In a phase 1b study, intravenous daratumumab plus pomalidomide and dexamethasone induced a very good partial response or better rate of 42% and was well tolerated in patients with heavily pretreated multiple myeloma. We aimed to evaluate whether daratumumab plus pomalidomide and dexamethasone would improve progression-free survival versus pomalidomide and dexamethasone alone in patients with previously treated multiple myeloma. Methods: In this ongoing, open-label, randomised, phase 3 trial (APOLLO) done at 48 academic centres and hospitals across 12 European countries, eligible patients were aged 18 years or older, had relapsed or refractory multiple myeloma with measurable disease, had an Eastern Cooperative Oncology Group performance status of 0–2, had at least one previous line of therapy, including lenalidomide and a proteasome inhibitor, had a partial response or better to one or more previous lines of antimyeloma therapy, and were refractory to lenalidomide if only one previous line of therapy was received. Patients were randomly assigned (1:1) by an interactive web-response system in a random block size of two or four to receive pomalidomide and dexamethasone alone or daratumumab plus pomalidomide and dexamethasone. Randomisation was stratified by number of previous lines of therapy and International Staging System disease stage. All patients received oral pomalidomide (4 mg, once daily on days 1–21) and oral dexamethasone (40 mg once daily on days 1, 8, 15, and 22; 20 mg for those aged 75 years or older) at each 28-day cycle. The daratumumab plus pomalidomide and dexamethasone group received daratumumab (1800 mg subcutaneously or 16 mg/kg intravenously) weekly during cycles 1 and 2, every 2 weeks during cycles 3–6, and every 4 weeks thereafter until disease progression or unacceptable toxicity. The primary endpoint was progression-free survival in the intention-to-treat population. Safety was analysed in all patients who received at least one dose of study medication. This trial is registered with ClinicalTrials.gov, NCT03180736 . Findings: Between June 22, 2017, and June 13, 2019, 304 patients (median age 67 years [IQR 60–72]; 161 [53%] men and 143 [47%] women) were randomly assigned to the daratumumab plus pomalidomide and dexamethasone group (n=151) or the pomalidomide and dexamethasone group (n=153). At a median follow-up of 16·9 months (IQR 14·4–20·6), the daratumumab plus pomalidomide and dexamethasone group showed improved progression-free survival compared with the pomalidomide and dexamethasone group (median 12·4 months [95% CI 8·3–19·3] vs 6·9 months [5·5–9·3]; hazard ratio 0·63 [95% CI 0·47–0·85], two-sided p=0·0018). The most common grade 3 or 4 adverse events were neutropenia (101 [68%] of 149 patients in the daratumumab plus pomalidomide and dexamethasone group vs 76 [51%] of 150 patients in the pomalidomide and dexamethasone group), anaemia (25 [17%] vs 32 [21%]), and thrombocytopenia (26 [17%] vs 27 [18%]). Serious adverse events occurred in 75 (50%) of 149 patients in the daratumumab plus pomalidomide and dexamethasone group versus 59 (39%) of 150 patients in the pomalidomide and dexamethasone group; pneumonia (23 [15%] vs 12 [8%] patients) and lower respiratory tract infection (18 [12%] vs 14 [9%]) were most common. Treatment-emergent deaths were reported in 11 (7%) patients in the daratumumab plus pomalidomide and dexamethasone group versus 11 (7%) patients in the pomalidomide and dexamethasone group. Interpretation: Among patients with relapsed or refractory multiple myeloma, daratumumab plus pomalidomide and dexamethasone reduced the risk of disease progression or death versus pomalidomide and dexamethasone alone and could be considered a new treatment option in this setting. Funding: European Myeloma Network and Janssen Research and Development.